The Implementation of Classroom Assessment (PBD) in Design and Technology (RBT) Education Among Primary Schools Teachers - Pua, Chee Chia; Ibrahim Mukhtar, Marina (Research and Innovation in Technical and Vocational Education and Training, 2024)
Malaysia is moving towards becoming a high-income and high-technology nation, in line with the goals of the 12th Malaysia Plan. In this context, Technical and Vocational Education and Training (TVET) plays a crucial role, with the subject of Life Skills now being replaced by Design and Technology (RBT). Classroom Assessment (PBD) for the RBT subject represents a new assessment approach in the national education system. This study aims to identify the level of PBA practices among RBT teachers in primary schools in the Johor Bahru district, as well as the challenges faced. It also examines the impact of these challenges on the effectiveness of teaching and learning, and the strategies used by teachers to overcome them. This study employs a mixed-method research design by using a survey for the first phase and then continuing the interviews to explain the challenges. 148 RBT teachers from primary schools in Johor Bahru were selected as respondents. Data were collected through a questionnaire covering respondents’ demographics, PBD practices, and implementation challenges. The results of the study show that the level of PBA practices among RBT teachers is high. However, there are major challenges such as student absenteeism, a vast syllabus, time constraints, and a lack of resources and technology. Teachers employ various strategies to overcome these challenges, including active parental involvement, administrative support, use of technology, and early planning. In conclusion, despite the challenges, the level of PBA practices among RBT teachers is high, and they employ various approaches to ensure effective teaching. This study has important implications for the Ministry of Education Malaysia in providing better support and resources to teachers.